Gothikana ebook - RuNyx (2023)
The eternal romance of Beauty and the Beast meets the gothic suspense of Dracula in this erotic dark academia story of epic love from bestselling author RuNyx. "RuNyx immerses her readers in the dark worlds she builds and then injects life into them in the most hauntingly beautiful way. Her work is unique and addictive—she really is one of a kind." —Hannah Grace, New York Times bestselling author of ICEBREAKER "Original, innovative, and unlike anything I've read before." ―L. J. Shen, USA Today bestselling author An unusual girl. An enigmatic man. An ancient castle. What could go wrong? An outcast her entire life, Corvina Clemm is left adrift after losing her mother. When she receives the admission letter from the mysterious University of Verenmore, she accepts it as a sign from the universe. The last thing she expects though is an old, secluded castle on top of a mountain riddled with secrets, deceit, and death. An enigma his entire life, Vad Deverell likes being a closed book but knowing exactly everything that happens in the university. A part-time professor working on his thesis, Vad has been around long enough to know the dangers the castle possesses. And he knows the moment his path crosses with Corvina, she's dangerous to everything that he is. They shouldn't have caught each other's eye. They cannot be. But a chill-inducing century-old mystery forces them to collide. People have disappeared every five years over the past century, Corvina is getting clues to unraveling it all, and Vad needs to keep an eye on her. And so begins a tale of the mysterious, the morbid, the macabre, and a deep love that blossoms in the unlikeliest of places. At the Publisher's request, this title is being sold without Digital Rights Management Software (DRM) applied.